Common pediatric medical procedures. Hip exam - Baum, Rebecca; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2018)
A complete review and demonstration of the pediatric hip exam, including assessment and indications for both infants and older children.
Presenter: Rebecca Baum.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 15, 2020)
Keywords: Hip joint -- Examination; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films